2011
DOI: 10.1152/ajprenal.00347.2010
|View full text |Cite
|
Sign up to set email alerts
|

Transient and sustained increases in glomerular permeability following ANP infusion in rats

Abstract: Axelsson J, Rippe A, Rippe B. Transient and sustained increases in glomerular permeability following ANP infusion in rats. Am J Physiol Renal Physiol 300: F24 -F30, 2011. First published October 13, 2010 doi:10.1152/ajprenal.00347.2010.-The present study was performed to investigate the effects of systemic atrial natriuretic peptide (ANP) infusion on the glomerular permeability to macromolecules in rats. In anesthetized Wistar rats (250 -280 g), the left urether was cannulated for urine collection while simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
2
14
0
1
Order By: Relevance
“…The slight (but significant) GFR changes are in accordance with our previous findings and those by others, showing a slight increase in GFR over time in Sham animals (5,7,9,39). This is probably related to increases in extracellular fluid volume and less blood sampling during the last period of the experiments.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The slight (but significant) GFR changes are in accordance with our previous findings and those by others, showing a slight increase in GFR over time in Sham animals (5,7,9,39). This is probably related to increases in extracellular fluid volume and less blood sampling during the last period of the experiments.…”
supporting
confidence: 92%
“…We have previously studied the glomerular permeability response to different biologically relevant challenges and observed varying patterns of response. For example, the responses to acute anaphylaxis, trauma, angiotensin II, and ANP seem to occur within min (3,4,7,9), whereas the response to e.g., hyperglycemia showed a lag time of ϳ20 min before any permeability increases were observed (5). Furthermore, with respect to the dynamics of permeability changes occurring over time, we have shown that ANP induces a biphasic permeability response, with an early permeability peak at 5 and 15 min and, after 30 min, a more sustained and low-grade increase in for Ficoll 70Å (7).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that CC16 is increased in urine following an exercise challenge test (Tufvesson et al 2013). Exercise increases glomerular permeability (Axelsson et al 2011), and we also found that both albumin and protein HC leaked into the urine along with CC16. Mannitol and EVH has also been shown to lead to a minor increase in urinary CC16 levels (Bolger et al 2011b, Kippelen et al 2013), although these challenges should not affect glomerular permeability.…”
Section: Discussionsupporting
confidence: 51%
“…The GFB is a dynamic barrier in which the permeability can change dramatically even in a short period of time (2)(3)(4)(5). The physiological and pathophysiological mechanisms behind the changes in permeability seem to be mediated primarily by the large-pore system.…”
Section: Discussionmentioning
confidence: 99%